1992
DOI: 10.1017/s0022112092000065
|View full text |Cite
|
Sign up to set email alerts
|

On transition due to three-dimensional disturbances in plane Poiseuille flow

Abstract: The purpose of the present study is to characterize the process of laminar–turbulent transition at Reynolds numbers which are subcritical from the two-dimensional linear point of view. The development of a point-like disturbance was studied in an air flow channel with hot-wire anemometry at a Reynolds number of 1600. Localized disturbances were triggered at one of the walls and their development followed downstream by traversing the hot-wire probe in the streamwise direction over a distance of 90 half channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…It has been demonstrated that velocity fluctuations around a laminar base flow exhibit high sensitivity to different sources of perturbations. This has provided reconciliation with experimental observations (Klebanoff et al 1962;Klebanoff 1971;Klingmann 1992;Westin et al 1994;Matsubara & Alfredsson 2001) that, even in the absence of modal instability, bypass transition can be triggered by large transient growth (Gustavsson 1991; Butler & Farrell 1992;Henningson & Reddy 1994;Schmid & Henningson 1994) or large amplification of deterministic and stochastic disturbances (Trefethen et al 1993;Farrell & Ioannou 1993b;Bamieh & Dahleh 2001;Jovanović 2004;Jovanović & Bamieh 2005). The non-normality of the linearized dynamical generator introduces interactions of exponentially decaying normal modes (Trefethen et al 1993;Schmid 2007), which in turn result in high flow sensitivity.…”
Section: Linear Analysis Of Transitional and Turbulent Shear Flowsmentioning
confidence: 67%
“…It has been demonstrated that velocity fluctuations around a laminar base flow exhibit high sensitivity to different sources of perturbations. This has provided reconciliation with experimental observations (Klebanoff et al 1962;Klebanoff 1971;Klingmann 1992;Westin et al 1994;Matsubara & Alfredsson 2001) that, even in the absence of modal instability, bypass transition can be triggered by large transient growth (Gustavsson 1991; Butler & Farrell 1992;Henningson & Reddy 1994;Schmid & Henningson 1994) or large amplification of deterministic and stochastic disturbances (Trefethen et al 1993;Farrell & Ioannou 1993b;Bamieh & Dahleh 2001;Jovanović 2004;Jovanović & Bamieh 2005). The non-normality of the linearized dynamical generator introduces interactions of exponentially decaying normal modes (Trefethen et al 1993;Schmid 2007), which in turn result in high flow sensitivity.…”
Section: Linear Analysis Of Transitional and Turbulent Shear Flowsmentioning
confidence: 67%
“…In the case of plane Poiseuille flow, the maximum streamwise fluctuations are expected near planes y = ±0.5h. The plane y = +0.5h is preferred to y = −0.5h due to the non-symmetric character of the injection (Klingmann 1992). The fluid is lit with a 1 mm thick light sheet and seeded with neutrally buoyant particles (d p ≈ 20 µm).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The temperature variation during the taking of a set of the measurements was monitored to ensure that the temperature drift of the flow from the calibration did not exceed more than 0.7 • C. The voltages of the hot-wire anemometer were acquired via an analog/digital converter with a sampling frequency of 20 kHz, and a sampling time of 30 s for a streamwise positioning measurement and 300 s for a detailed measurement at the most downstream position. A wedge mechanism modeled on that used by Klingmann 26 was employed for probe positioning in the wall-normal direction. It was attached at the ends of two 2300 mm long bars and was moved by a linear actuator in the streamwise direction.…”
Section: B Measurement Techniquementioning
confidence: 99%